Suspension of control matrices through touch (REVISTA NODO, 2025)
This research-creation project emerges from an expanded notion of touch —understood as a specific, performative practice within multimedia art— as both movement and interface that generates worlds. I propose that this approach holds the potential to increase happiness by liberating us from certain control matrices. Through touch —fundamentally a relational act— I explore modes of mediating existence and transforming it (while simultaneously transforming ourselves) via a broad spectrum of techniques, procedures, machines, and arts. This work begins with suspension as an action that disrupts the Cartesian segmentation of the senses as distinct categories, aiming to expand the inquiry into the relationships between artistic practices and happiness, and between image and technique-technology. To this end, I introduce the concept of artécnica (art-technique), conceived as a way to establish an indispensable dialogue between making and thinking. The research seeks to deepen our understanding of this relationship and the potential of practice to transmute “difficulties into means”. Adopting an experiential, situated-knowledge approach, I engage with concepts drawn from sociology and art theory, as well as those generated at the intersection of art and technique. Suspensión investigates the political-affective dimension of electronic arts and explores haptics as a gateway to alternative modes of perception.
Keywords: Arte; Artechnic; electronic art; Generative Art; artificial intelligence; touch